Women in the Wilderness The »Female Legislation« of the Book of Numbers (Num 5,11-31; 27,1-11; 30,2-17) - Cocco, Francesco (Mohr Siebeck, 2020)
Frauen in der Wildnis. Weibliche Gesetzgebung im Buch Numeri (Num 5,11-31; 27,1-11; 3,2-17).
PublicationDate: 20200707
Keywords: Biblical Law -- Women -- Freies Christentum -- Wilderness -- Altes Testament -- Array